Abusive head trauma in children: a literature review - Nahara R.L. Lopes; Evelyn Eisenstein; Lúcia C.A. Williams (Elsevier, 2013)
Objective: To review the scientific literature on pediatric abusive head trauma as a form of physical abuse against infants and young children, highlighting the prevalence, signs and symptoms, consequences, risk factors for its occurrence, and prevention strategies. Data source: The MEDLINE, SciELO, LILACS, and Web of Science databases from 2001 to 2012 were reviewed, using the terms "shaken baby syndrome" and "abusive head trauma" in English, Spanish, and Portuguese. Data synthesis: Pediatric abusive head trauma is defined as injury to the skull or intracranial contents of a infant or child younger than 5 years due to intentional abrupt impact and/or violent shaking. It occurs mainly in infants and children under 1 year of age, and may result in severe consequences, from physical or mental disabilities to death. Although there are specific signs for this form of abuse, they can be mistaken for common illnesses in children or accidental head injury; thus, clinical training of professionals involved in the assessment of cases to attain the correct diagnosis is crucial. Prevention strategies should include early identification of cases, as well as parental education on child development, especially on the infant's crying pattern. Conclusions: Considering the severity of abusive head trauma in children, it is critical that prevention strategies be implemented and evaluated in the Brazilian context. It is suggested that its incidence indicators be assessed at the national level. Resumo: Objetivo: Fornecer uma revisão de literatura científica sobre trauma craniano violento pediátrico enquanto forma de maus-tratos físicos contra bebês e crianças, ressaltando prevalência, sinais e sintomas, consequências, fatores de risco para sua ocorrência e, principalmente, estratégias de prevenção. Fontes dos dados: Revisão nas bases de dados MEDLINE, SciELO, LILACS e Web of Science no período de 2001 a 2012 utilizando os termos "síndrome do bebê sacudido" e "trauma craniano violento" em inglês, espanhol e português. Síntese dos dados: O trauma craniano violento é definido como a lesão ao crânio ou ao conteúdo intracraniano de um bebê ou criança menor de cinco anos devido a um impacto brusco intencional e/ou a uma sacudida violenta. Ocorre principalmente com bebês e crianças menores de um ano de idade, e pode resultar em consequências graves, desde deficiências físicas ou mentais até a morte. Apesar de haver sinais específicos para esta forma de maus-tratos, eles podem se confundir com doenças comuns em crianças ou traumas cranianos acidentais, sendo imprescindível o preparo clínico dos profissionais envolvidos na avaliação dos casos para o diagnóstico correto. As estratégias de prevenção devem incluir tanto a identificação precoce dos casos, como a educação parental sobre o desenvolvimento infantil, especialmente sobre o padrão de choro do bebê. Conclusões: Considerando a gravidade do trauma craniano violento pediátrico, é fundamental que estratégias de prevenção sejam implementadas e avaliadas no contexto brasileiro. Sugere-se que indicadores de sua incidência sejam pesquisados nacionalmente. Keywords: Abusive head trauma, Shaken baby syndrome, Child maltreatment, Physical violence, Palavras-chave: Trauma craniano violento, Síndrome do bebê sacudido, Maus-tratos infantis, Violência física